Stigma in the marketplace - Rocha, Rodolfo Rodrigues (2023)
Stigma is a discrediting attribute that emerges in social interactions, playing different roles in different contexts. Several fields (e.g., sociology and psychology) have been dedicating special attention to this phenomenon as it significantly impacts people\'s lives. Although there is some interest in the idiosyncrasies of stigma in marketing and consumer behavior, the literature investigating such a concept is still too fragmented. By exploring the roles of stigma in the marketplace from multiple perspectives, this dissertation deepens and advances the understanding of the complex relationship between stigma and the marketplace. The first paper is a systematic literature review that synthesizes what we know about stigma in the marketplace. It also suggests research avenues worth exploring by marketing and consumer behavior researchers to advance knowledge on marketplace stigma. The second article is a qualitative study looking at stigmatized consumers. It examines the meanings of intimate apparel consumption to transgender consumers and the interplay between stigma and vulnerability in the marketplace. The third and last article comprises two experimental studies that reveal the negative impacts of conflicting information, within and across different information sources, on consumers\' attitudes toward and willingness to adopt medical cannabis. This set of papers shows that stigma plays complex and multifaceted roles in the marketplace, affecting consumers, companies, and other marketplace stakeholders.